Dynamic MicroRNA Expression Profiles During Embryonic Development Provide Novel Insights Into Cardiac Sinus Venosus/Inflow Tract Differentiation - Garcia-Padilla, Carlos; Dueñas, Angel; Franco, Diego; Garcia-Lopez, Virginio; Aranega, Amelia; Garcia-Martinez, Virginio; Lopez-Sanchez, Carmen (Frontiers in Cell and Developmental Biology, 2022)
MicroRNAs have been explored in different organisms and are involved as molecular switches modulating cellular specification and differentiation during the embryonic development, including the cardiovascular system. In this study, we analyze the expression profiles of different microRNAs during early cardiac development. By using whole mount in situ hybridization in developing chick embryos, with microRNA-specific LNA probes, we carried out a detailed study of miR-23b, miR-130a, miR-106a and miR-100 expression during early stages of embryogenesis (HH3 to HH17). We also correlated those findings with putative microRNA target genes by means of mirWalk and TargetScan analyses. Our results demonstrate a dynamic expression pattern in cardiac precursor cells from the primitive streak to the cardiac looping stages for miR-23b, miR-130a and miR-106a. Additionally, miR-100 is later detectable, during cardiac looping stages (HH15-17). Interestingly, the sinus venosus/inflow tract showed to be the most representative cardiac area for the convergent expression of the four microRNAs. Through in silico analysis we revealed that distinct Hox family members are predicted to be targeted by the above microRNAs. We also identified expression of several Hox genes in the sinus venosus at stages HH11 and HH15. In addition, by means of gain-of-function experiments both in cardiomyoblasts and sinus venosus explants, we demonstrated the modulation of the different Hox clusters -Hoxa, Hoxb, Hoxc and Hoxd- genes by these microRNAs. Furthermore, we correlated the negative modulation of several Hox genes, such as Hoxa3, Hoxa4, Hoxa5, Hoxc6 or Hoxd4. Finally, we demonstrated through a dual luciferase assay that Hoxa1 is targeted by miR-130a and Hoxa4 is targeted by both miR-23b and miR-106a, supporting a possible role of these microRNAs in Hox gene modulation during differentiation and compartmentalization of the posterior structures of the developing venous pole of the heart.